2016
DOI: 10.1002/admi.201600760
|View full text |Cite
|
Sign up to set email alerts
|

Gas–Liquid Cold Plasma for Synthesizing Copper Hydroxide Nitrate Nanosheets with High Adsorption Capacity

Abstract: A facile, fast and environmentally friendly gas–liquid plasma method for synthesizing Cu2(OH)3NO3 nanosheets is reported for the first time. The preparation process just takes 12 min using Cu(NO3)2 aqueous solution without any other chemical agents. The Cu2(OH)3NO3 nanosheets exhibit much higher methyl orange (MO) adsorption capacity (428.8 mg MO g−1) than that prepared by the solvothermal method (212.8 mg MO g−1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 51 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Because STEM observation showed no large particles, no Tyndall phenomenon was observed, and colloid was stable for 1 year without sedimentation; it is assumed that all particles in LAL-Cu colloid was converted to small particles by LAAL. Cu-based nanoparticles have been synthesized by various methods; , however, although monodispersed nanoparticles have been fabricated, Cu-based nanoparticles with sizes as small as those in the present study have not been reported. The mechanism to produce these very small nanoparticles has been discussed as below. , In the case of LAL, a high density plasma is produced because the expansion of the plasma induced by LAL is confined by the liquid (confinement effect) unlike the free expansion in a vacuum, which results in a high collision possibility.…”
Section: Resultsmentioning
confidence: 78%
“…Because STEM observation showed no large particles, no Tyndall phenomenon was observed, and colloid was stable for 1 year without sedimentation; it is assumed that all particles in LAL-Cu colloid was converted to small particles by LAAL. Cu-based nanoparticles have been synthesized by various methods; , however, although monodispersed nanoparticles have been fabricated, Cu-based nanoparticles with sizes as small as those in the present study have not been reported. The mechanism to produce these very small nanoparticles has been discussed as below. , In the case of LAL, a high density plasma is produced because the expansion of the plasma induced by LAL is confined by the liquid (confinement effect) unlike the free expansion in a vacuum, which results in a high collision possibility.…”
Section: Resultsmentioning
confidence: 78%
“…The characteristic peaks were observed in the XRD patterns of the unheated samples prepared from the solutions of pH 3.07, pH 3.90, and pH 4.57 on the Ag-deposited TiO 2 films during the UV irradiation, as shown in Figure 1. All the samples exhibited peaks at 2θ = 12.8 • and 25.7 • assigned to the (001) and (200) planes, respectively, of Cu 2 (OH) 3 (NO 3 ), i.e., layered copper hydroxide (LCH) nitrate [21,22]. CuO was not observed under the present conditions similar to the layered zinc hydroxide (LZH) nitrate in the case of the ZnO formation [14,15].…”
Section: Characterization Of the Film Surfacementioning
confidence: 75%
“…There is no obvious difference between them. Cu2p XPS spectra (Figure 5c) present the main peaks of copper, and the satellite peaks corresponding to copper (II) were observed in all four samples [48]. The Cu2p3/2 spectra in CO-240 can be deconvoluted into two peaks at 933.7 eV and 933.0 eV, corresponding to Cu (II) and Cu (I) due to the reduction of CO.…”
Section: Effect Of Activating Atmosphere On Cubtc Catalystsmentioning
confidence: 93%